APLIKASI PEMANTAUAN KOMPOR GAS BERBASIS INTERNET OF THINGS MENGGUNAKAN ANDROID - Zulfani, Zulfani; Qadriah, Laila; Achmady, Sayed; Salat, Junaidi (Jurnal Sains Riset, 2022)
The number of cases of fires and accidents caused by the leakage and explosion of LPG gas cylinders is a frightening thing for most people who use LPG gas. There are various factors that cause explosions or fires on LPG, including leaks in gas hoses, gas cylinders or gas regulators that are not installed properly. In addition, the factor of human error (human error) can also be a factor in the explosion of LPG gas. One example is forgetting to turn off the stove after finishing cooking. As technology and IoT (Internet of Things) develop, an IoT (Internet of Things)-based Android application has been developed. This application can monitor and control gas stoves remotely. If there is a leak and fire on the gas stove, the IoT (Internet of Things) system can turn off the gas stove automatically or be controlled manually.Keywords : Android App, Microcontroller, Internet of Things, Wemos D1 Mini